2021
DOI: 10.1292/jvms.20-0742
|View full text |Cite
|
Sign up to set email alerts
|

Broad detection and quick differentiation of bovine viral diarrhea viruses 1 and 2 by a reverse transcription loop-mediated isothermal amplification test

Abstract: For broad detection of pestivirus A (bovine viral diarrhea virus 1: BVDV1) and pestivirus B (BVDV2) by a reverse transcription loop-mediated isothermal amplification (RT-LAMP) test, the P25 primer set was designed using nucleotide sequences of 5'-untranslated region of 1454 BVDVs.The base coverage of each primer against diverse BVDVs were more than 99% in each base position.The one step LAMP test with the P25 primer set could detect both BVDV1 (TK) and BVDV2 (KZ), but did not amplify 5 other bovine viruses. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…P25 primers were able to detect both strains with higher sensitivity compared to primers of previous study by Aebischer et al However, authors reported that P25 primer set weakly cross-reacts with pestivirus D and H. In clinical samples, BVDV RT-LAMP test had comparable results with RT-qPCR. An additional species-specific primer set (P26) designed to differentiate BVDV-1 from BVDV-2 as well [ 60 ].…”
Section: Ruminant Viral Diseases and Lamp Assays For Diagnosismentioning
confidence: 99%
“…P25 primers were able to detect both strains with higher sensitivity compared to primers of previous study by Aebischer et al However, authors reported that P25 primer set weakly cross-reacts with pestivirus D and H. In clinical samples, BVDV RT-LAMP test had comparable results with RT-qPCR. An additional species-specific primer set (P26) designed to differentiate BVDV-1 from BVDV-2 as well [ 60 ].…”
Section: Ruminant Viral Diseases and Lamp Assays For Diagnosismentioning
confidence: 99%
“…Bovine viral diarrhea virus (BVDV), the cause of bovine viral diarrhea (BVD) disease, belongs to the family Flaviviridae genus Pestivirus [ 1 ]. Among 11 different species of Pestivirus (A-K), species A and B, known as BVDV-1 and BVDV-2 respectively, are the most important [ 2 ]. The BVDV contains a positive-sense single-stranded RNA (12.3–16.5 kb) encoding four structural and eight non-structural proteins [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques are implemented for the detection of acute or persistent BVDV infections. These techniques include virus isolation, PCR-based methods, ELISAs and more recent techniques such as loop-mediated isothermal amplification (LAMP), dot-blot assay [ 2 , 16 18 ]. Since these methods are laborious, time and cost-consuming, developing new accurate and rapid detection techniques such as biosensors, as a new generation of sensing technology, is essential.…”
Section: Introductionmentioning
confidence: 99%